The genotype–phenotype correlations of the CACNA1A-related neurodevelopmental disorders: a small case series and literature reviews - Kessi, Miriam; Chen, Baiyu; Pang, Nan; Yang, Lifen; Peng, Jing; He, Fang; Yin, Fei (Frontiers in Molecular Neuroscience, 2023)
Background: Genotype-phenotype correlations of the CACNA1A-related neurodevelopmental disorders such as global developmental delay (GDD) / intellectual disability (ID), epileptic encephalopathy (EE), and autism spectrum disorder (ASD) are unknown. We aimed to summarize genotype-phenotype correlations, and potential treatment for CACNA1A-related neurodevelopmental disorders.Methods: Six children diagnosed with CACNA1A-related neurodevelopmental disorders at Xiangya Hospital, Central South University from April 2018 to July 2021 were enrolled. PubMed database was systematically searched for all reported patients with CACNA1A-related neurodevelopmental disorders until February 2023. Thereafter, we divided patients into several groups for comparisons.Results: Six patients were recruited from our hospital. Three cases presented with epilepsy, 5 with GDD/ID, 5 with ataxia, and 2 with ASD. The variants included p.G701R, p.R279C, p.D1644N, p.Y62C, p.L1422Sfs*8, and p. R1664Q (2 gain-offunction (GOF) and 4 loss-of-function (LOF) variants. About 187 individuals with GDD/ID harbouring 123 variants were found (case series plus data from literatures). Of those 123 variants, p.A713T and p.R1664* were recurrent, 37 were LOF, and 7 were GOF. GOF variants were linked with severe-profound GDD/ID while LOF variants were associated with mild-moderate GDD/ID (P=0.001). The p.A713T variant correlated with severe-profound GDD/ID (P=0.003). A total of 130 epileptic patients harbouring 83 variants were identified. The epileptic manifestations included status epilepticus (n=64), provoked seizures (n=49), focal seizures (n=37)), EE (n=29), absence seizures (n=26), and myoclonic seizures (n=10). About 49 (42.20%) patients had controlled seizures while 67 (57.80%) individuals remained with refractory seizures. Status epilepticus correlated with variants located on S4, S5 and S6 (P=0.000). Among the 83 epilepsy-related variants, 23 were recurrent, 32 were LOF, and 11 were GOF. Status epilepticus was linked with GOF variants (P=0.000). LOF variants were associated with absence seizures (P=0.000). Six patients died at early age (3 months to ≤ 5 years). We found 18 children with ASD. Thirteen variants including recurrent ones were identified in those 18 cases. GOF changes were more linked to ASD.The p.A713T variant is linked with severe-profound GDD/ID. More than half of CACNA1A related epilepsy is refractory. The most common epileptic manifestation is status epilepticus, which correlates with variants located on S4, S5 and S6.